Every something is an echo of nothing : an exploration into an interconnectedness between a daily walking regimen and art : an exegesis presented in partial fulfilment of the requirements for a degree of Master of Fine Arts at Massey University, Wellington, N.Z. - Mooney, Rebecca (Massey University, 2019)
Physical engagement with the landscape informs my artistic practice. This connection includes a daily walking regimen informed by a Buddhist sensibility. The Wellington Botanic Garden is close to my home, and I walk there each morning. It's through this familiar encounter within a specific site that I closely observe my immediate surroundings. It has been chosen as a site to gather the imagery from, to support my research into the relationship between walking and an artistic practice. I discuss the role that phenomenological perception of colour, time, space and movement play in understanding my perception of spatial beauty, expanded by the study of eastern painting aesthetics. This study documents my journey as I moved from paintbrushes to using video projection as a tool to further explore the phenomenological relationships between the perceiver and the perceived. I focus on my interpretation of sights and happenings and channel these sensory experiences into projections of flora as primary media. The viewer is encouraged to slow down and pay attention to what is happening around them by viewing the work in an exhibition space. I believe that it is essential to stay physically connected with the Earth. Because I see there is enough negativity and criticism in the world already, this ongoing journey focuses on developing imagery that offers a heartfelt creative gesture of kindness and positivity.
Possibly copyrighted Figures remain for the sake of clarity.
Keywords: 360604 Photography, video and lens-based practice